Biological Anthropology in Poland: Its History and Short Scientific Biographies of the Contributing Professors - Kaszycka, Katarzyna A. (Anthropological Review, 2025)
The year 2025 marks exactly one hundred years since the founding of the Polish Anthropological Society in Poznań (November 12, 1925), initiated by Professor Adam Wrzosek of the University of Poznań, who became its first president, as well as the 150th anniversary of Adam Wrzosek’s birth. This year also marks the 120th anniversary of the establishment, on the initiative of Kazimierz Stołyhwo, of the first institution devoted to physical anthropology in Poland and the first in Eastern Europe: The Anthropological Laboratory at the Museum of Industry and Agriculture in Warsaw (1905). Year 2026 will record the centenary of the publication of the first volume of the Polish Anthropological Society journal “Przegląd Antropologiczny”, now “Anthropological Review” (1926), and the 170th anniversary of the beginning of anthropology as a university discipline (1856), considered the year when the first anthropology lectures were given at the Jagiellonian University in Kraków by Professor Józef Majer. A number of works devoted to the history of physical/biological anthropology in Poland have been documented in the literature, especially the history of individual centers, published in the 1950s on the occasion of the 100th anniversary of the discipline in 1956, as well as studies on the history of Polish anthropology in a more comprehensive approach on other occasions. This article explores the history of biological anthropology in Poland, narrated mostly through short biographies of its founders – the professors whose work and achievements contributed to the development of the discipline, becoming part of the history of science. The biographical histories essentially cover the 19th and 20th centuries and include the professors who have either already made history or who have turned 75 on the date of publication of this article (born up to 1950).